Wavelet analysis and NDT for condition assessment of historic Masonry Bridge. (November 2022) - Kilic, Gokhan
Abstract: Maintaining a country's heritage requires the implementation of methods that enable the condition assessment of historic infrastructure, preferably with zero damage/interventions and minimum post-inspections. Non-Destructive Techniques (NDT) can meet such criteria in a timely and cost-efficient manner. These techniques include High Definition and Infrared Thermography (IRT) drone systems to assess sub-surface state and detect external heritage defects, and Ground Penetrating Radar (GPR) to detect internal defects. The focus of the research is on the implementation of a Wavelet Analysis, a neural network-based method which combines the use of these NDT techniques to maximize information range and accuracy. The comprehensive approach adopted in this study is able to accurately identify the location and size of superficial and internal defects by collecting appropriate data from heritage structures from the Historical Masonry Bridge at Hypokremnos (Icmeler) in Turkey.